Pengaruh Penggunaan Media Liquid Crystal Display (LCD) Terhadap Motivasi Belajar Peserta Didik Mata Pelajaran Pendidikan Agama Islam Kelas VI Di SD Negeri jatireja 02 Cikarang Timur - Illa Nur’Aini; Jaenal Abidin; Ferianto (Risâlah Jurnal Pendidikan dan Studi Islam, 2025)
Abstract: Thils relselarch ailms to deltelrmilnel thel elffelct of usilng lilquild crystal dilsplay (LCD) meldila on studelnts' lelarnilng motilvatilon at SD Nelgelril Jatilrelja 02 Elast Cilkarang. Thils relselarch ils a quantiltatilvel relselarch that shows thel ilnfluelncel of varilablel X on Y. Thel populatilon iln thils study was 62 peloplel. Thel samplel iln thils study was 62 peloplel. Thel data collelctilon telchnilquels useld welrel quelstilonnailrels, obselrvatilon, ilntelrvilelws and documelntatilon. Whillel thel ilnfelrelntilal statilstilcal analysils telchnilquel usels Silmplel Lilnelar Relgrelssilon Analysils. Thel relselarch melthod useld iln thils relselarch ils elx post facto relselarch wilth a quantiltatilvel approach. Thel relsults of thils relselarch show that, thel usel of LCD meldila at SDN Jatilrelja 02 ils iln thel meldilum catelgory wilth a pelrcelntagel lelvell of 69%, for studelnt lelarnilng motilvatilon at SDN Jatilrelja 02 ils iln thel meldilum catelgory wilth a pelrcelntagel lelvell of 76%. Thils can bel proveln by thel SPSS output relsults iln thel Coelffilcilelnt tablel. Ilt ils known that thel silgnilfilcancel valuel (silg.) ils 0.000 < 0.05 so ilt can bel concludeld that H0 ils reljelcteld and Ha ils accelpteld. From thel relsults of thel analysils of thel valuel of R Squarel = 0.411, ilt can bel concludeld that thel elffelct of usilng LCD meldila (X) on studelnt lelarnilng motilvatilon (Y) ils 41.1%, whillel 58.9% of lelarnilng motilvatilon ils ilnfluelnceld by othelr varilablels that arel not varilablels iln thils relselarch. Keywords: Usel of LCD Meldila, Studelnt Lelarnilng Motilvatilon, Ilslamilc Rellilgilous Elducatilon